ABOUT PREPARATION AND QUALIFYING DESCRIPTION OF TEACHERS OF DRAWING IN UKRAINE OF THE XIX CENTURY - I. Krasyuk (Academy of Cognitive and Natural Sciences, 2022)
In the article the requirements are examined to the teachers of drawing in folk formation of Ukraine in XIX and beginning of XX century. On the basis of analysis of normative documents is traced evolution maintenances of the proper personnel training for different links of school formation of that time.